75th Anniversary Banquet (The Southern African Institute of Mining and Metallurgy)
A banquet, attended by 467 members and visitors, was held at the Wanderers Club, Johannesburg, at 8 p.m. on Friday, 21st March, 1969, to celebrate the 75th Anniversary of the founding of the Institute. Introduction of Dr Carel de Wet R. C. J. Goode (President) Dames en here: Ons het 'n aantal vooraanstaande gaste in ons midde vanaand en mnr Maxwell sal u later meer van hulle vertel. Dit is my aangename plig om u voor te stel aan sy Edele, die Minister van Mynwese, van Beplanning, en van Gesondheid, Dr de Wet en sy gade, mev de Wet. Sy Edele Dr de Wet het geen bekendstelling nodig nie-alhoewel hy ons minister vir slegs die afgelope twee jaar is, het hy reeds talle funksies van ons Mynbedryf bygewoon en het baie vriende gemaak onder ons. Hy het homself baie bemind onder ons gemaak toe hy Wes-Driefontein onlangs besoek het om hulle ondersteuning en aanmoediging aan te bied in hulle uur van nood. The Honourable Dr de Wet was born in the Free State. He is a grandson of that very famous general Christiaan de Wet, who caused so much pain to the British forces and for so many months so successfully eluded them in the Transvaal and Orange Free State. He was educated at both the Pretoria and Witwatersrand Universities. He first practised medicine at Boksburg and then moved to Vanderbijlpark, so you see he has an early association with gold mining on the Witwatersrand, and in moving to the Vereeniging-Vanderbijlpark district he became closely involved in our coal mining and metallurgical industries. South Africa's first steel was poured from a l0-ton open hearth furnace belonging to the Union Steel Corporation in Vereeniging in 1913. Dr de Wet has been mayor of Vanderbijlpark and for several years has been their member of parliament. More recently, the Honourable Dr de Wet has filled with great honour that most important office of Ambassador for the Republic of South Africa in London. At present he wears two hats, in that he is Minister of Planning and of Health, but more important is his cloak, that of Minister of Mines, which I trust offers him the greatest comfort. To fulfill these three arduous tasks must demand of him a terrific devotion to duty, and in doing this he carries on that loyal tradition of service to his fatherland so evident in his grandfather. Dames en here, dit is vir my 'n groot genoeë om Sy Edele Dr de Wette vra om 'n heildronk in te stel op die Instituut vir Mynwese en Metallurgie. Toast to the Institute of Mining and Metallurgy Dr the Honourable C. de Wet (Minister of Mines): Mr President, ladies and gentlemen, Mr President you have introduced me gracefully to this distinguished company and I am appreciative of your remarks. I am fully conscious of the responsibilities that devolve upon me as Minister of Mines in a country where mining makes so vital a contribution to economic progress and development and has, in fact, laid much of the foundation on which our present proud edifice is built. The achievements of the mining and metallurgical industry in its diversified activities arouse feelings equivalent to paternal pride, but let me speedily add that in considering any family relationship that may exist, the Minister of Mines should not be regarded in the role either of a fairy godmother or an indulgent father.